2023
DOI: 10.1063/5.0146491
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the bubble collapse energy using the electrohydrodynamic force

Abstract: The energy released during the bubble collapse process is used for medical and industrial purposes. The present study investigates the effects of electrohydrodynamic force on the collapse phenomenon near the rigid wall and the enhancement of the collapse energy. A solver in the OpenFoam open-source code is developed based on the volume-of-fluid model, in which the effects of compressibility, energy transfer, and electrohydrodynamic force are included. The developed solver is validated against the available exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…In contrast, the regular jet has a speed of the order of 80 m s −1 that increases slowly with γ . The micro-jet shape and velocity are dependent on the particular flow conditions, where acoustic (Rosselló et al 2018) and electric fields (Taleghani et al 2023), bubble interaction (Han et al 2015), and the presence of more than one boundary have been reported to affect the velocity.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the regular jet has a speed of the order of 80 m s −1 that increases slowly with γ . The micro-jet shape and velocity are dependent on the particular flow conditions, where acoustic (Rosselló et al 2018) and electric fields (Taleghani et al 2023), bubble interaction (Han et al 2015), and the presence of more than one boundary have been reported to affect the velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Much research in boiling has been aimed at developing and enhancing the geometry of a particular surface to increase nucleation, reduce the surface superheat temperature, and delay the CHF [11][12][13][14][15]. A large number of methods are proposed, which are divided into active methods [16][17][18][19] and passive methods [20][21][22]. Passive methods include rough surfaces [23], porous and hydrophilic surfaces [24,25], nanoparticle addition to the base fluid [26][27][28], and surface expansion and using fins [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…They observed nanofluid had a higher critical heat flux than critical heat flux of boiling, and the highest CHF was related to ferrofluid and was 2.6 times higher than pure water. This is because of the accumulation of nanoparticles on the surface and increased surface wettability [31].…”
Section: Introductionmentioning
confidence: 99%